Pengaruh Model Pembelajaran Survey, Question, Read, Recite, Reflect, Review (SQ4R) terhadap Motivasi Belajar Siswa - Diora Gustina; Tontowi Amsia; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2018)
The purpose of this research is to find out the influence of Survey, Question, Read, Recite, Reflect, Review (SQ4R) learning model on students' learning motivation in History subject for students of grade XI Social Science class of Senior High School 1 Banjit academic year of 2017/2018. This research applied One Group Pretest-Posttest Design as its research design. The population in this research was taken from students of grade XI Social Science class Senior High School 1 Banjit. The sample of the research was carried out using Saturated Sampling technique. The data analysis technique was done through quantitative data analysis with Theta formula. The result showed that from the quantitative data analysis using the Theta formula, it can be concluded that: "There is a positive influence of moderate 0.50 of the Survey, Question, Read, Recite, Reflect, Review, (SQ4R) learning model on Students' Motivation in History Subject of students grade XI Social Science Senior class Senior High School 1 Banjit academic year of 2017/2018.Tujuan penelitian ini adalah untuk mengetahui adanya pengaruh Model Survey, Question, Read, Recite, Reflect, Review (SQ4R) terhadap motivasi belajar siswa pada Mata Pelajaran Sejarah Kelas XI IPS SMA Negeri 1 Banjit Tahun Ajaran 2017/2018”. Penelitian ini menggunakan desain penelitian One Group Pretest-Posttest Design. Populasi dalam penelitian ini adalah siswa Kelas XI IPS SMA Negeri 1 Banjit. Sampel dipilih menggunakan teknik Sampling Jenuh. Teknik analisis data dalam penelitian ini adalah analisis data kuantitatif dengan dilakukan uji analisis data dengan rumus Theta. Berdasarkan analisis data secara kuantitatif dengan menggunakan rumus Theta dapat ditarik kesimpulan  bahwa “Ada pengaruh positif yang cukup berarti atau sedang yaitu 0,50 dari Model Survey, Question,Read, Recite, Reflect, Review, (SQ4R) terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Sejarah Kelas XI IPS SMA Negeri 1 Banjit Tahun Ajaran 2017/2018. Kata kunci: model, motivasi belajar, pengaruh